Language dysfunction-associated EEG findings in patients with CAR-T related neurotoxicity. Issue 1 (18th June 2020) - Sokolov, Elisaveta; Karschnia, Philipp; Benjamin, Reuben; Hadden, Robert D M; Elwes, Robert C D; Drummond, Lee; Amin, Devyani; Paiva, Vitor; Pennisi, Alex; Herlopian, Aline; Frigault, Matthew; Sanderson, Robin; et al.
Abstract : Chimeric antigen receptor-modified T cells (CAR-T) have emerged as a promising immunotherapeutic approach in relapsed/refractory haematolgical malignancies. Broader application is limited by unique toxicities, notably, neurotoxicity (NTX). Language dysfunction is among the most frequent symptoms of NTX, the underlying mechanisms of which remain to be elucidated. Electroencephalogram (EEG) is an important tool to monitor for NTX and may provide insights into language dysfunction. Aim: We aimed to characterise language dysfunction and define electroencephalographic signatures after CAR-T cell therapy. Methods: We reviewed the clinical presentation and EEG findings of 20 adult patients presenting with language dysfunction after CAR-T cell infusion. The cohort included a subset of patients treated with investigational CD19-directed CAR-T cells for non-Hodgkin's lymphoma (n=17), acute lymphoblastic leukaemia (n=1), follicular lymphoma (n=1) and chronic lymphocytic leukaemia (n=1). Results: Language dysfunction presented within 14 days of CAR-T cell infusion in 16 (84%) patients. Ten (50%) patients had mild word-finding difficulties and 10 (50%) had marked dysphasia with profound word-finding difficulties; the latter were all associated with generalised rhythmic delta activity or generalised periodic discharges on EEG. Conclusions: Language dysfunction after CAR-T cell therapy is associated with generalised EEG abnormalities.